The insecticide chlorpyrifos modifies the expression of genes involved in the PXR and AhR pathways in the rainbow trout, Oncorhynchus mykiss - De Anna, JS; Darraz, LA; Painefilú, JC; Cárcamo, JG; Moura-Alves, P; Venturino, A; Luquet, CM (Elsevier, 2021)
Chlorpyrifos (CPF) is an organophosphate pesticide, commonly detected in water and food. Despite CPF toxicity on aquatic species has been extensively studied, few studies analyze the effects of CPF on fish transcriptional pathways. The Pregnane X receptor (PXR) is a nuclear receptor that is activated by binding to a wide variety of ligands and regulates the transcription of enzymes involved in the metabolism and transport of many endogenous and exogenous compounds. We evaluated the mRNA expression of PXR-regulated-genes (PXR, CYP3A27, CYP2K1, ABCB1, UGT, and ABCC2) in intestine and liver of the rainbow trout, Oncorhynchus mykiss, exposed in vivo to an environmentally relevant CPF concentration. Our results demonstrate that the expression of PXR and PXR-regulated genes is increased in O. mykiss liver and intestine upon exposure to CPF. Additionally, we evaluated the impact of CPF on other cellular pathway involved in xenobiotic metabolism, the Aryl Hydrocarbon Receptor (AhR) pathway, and on the expression and activity of different biotransformation enzymes (CYP2M1, GST, FMO1, or cholinesterases (ChEs)). In contrast to PXR, the expression of AhR, and its target gene CYP1A, are reduced upon CPF exposure. Furthermore, ChE and CYP1A activities are significantly inhibited by CPF, in both the intestine and the liver.